2004
DOI: 10.1089/088922204322749468
|View full text |Cite
|
Sign up to set email alerts
|

HLA Allele Sharing and HIV Type 1 Viremia in Seroconverting Zambians with Known Transmitting Partners

Abstract: Rapid HIV type 1 (HIV-1) mutation coupled with immune evasion poses a major obstacle to effective interventions. In particular, transmission of HIV-1 from a donor partner (transmitter) to a recipient (seroconverter) with similar antigen-presenting molecules (i.e., human leukocyte antigens, HLA) may favor or expedite viral adaptation to host immune responses. Our PCR-based HLA-A, HLA-B, and HLA-DRB1 genotyping for 115 Zambian couples with documented intracouple HIV-1 (mostly clade C) transmission revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
64
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(74 citation statements)
references
References 51 publications
10
64
0
Order By: Relevance
“…In contrast, a more significant VL correlation was shown for a transmission pair cohort of men who have sex with men (MSM) in San Francisco (21), and a phylogenetic analysis of MSM in the Swiss HIV Cohort Study concluded that up to half of the variance in set-point VL can be heritable (22). These observations reinforced the hypothesis that the genetic characteristics of the transmitted founder virus could be an important determinant for defining the early set-point VL in the linked SC (18,19,21,22). The contribution of the virus may, however, be modulated by human genetic factors in both the SC and the TSP.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…In contrast, a more significant VL correlation was shown for a transmission pair cohort of men who have sex with men (MSM) in San Francisco (21), and a phylogenetic analysis of MSM in the Swiss HIV Cohort Study concluded that up to half of the variance in set-point VL can be heritable (22). These observations reinforced the hypothesis that the genetic characteristics of the transmitted founder virus could be an important determinant for defining the early set-point VL in the linked SC (18,19,21,22). The contribution of the virus may, however, be modulated by human genetic factors in both the SC and the TSP.…”
mentioning
confidence: 85%
“…This observation is consistent with our previous studies of the ZEHRP cohort and with other studies of heterosexual cohorts of limited size. These studies demonstrated a relatively weak correlation between VLs in TSPs and SCs in linked heterosexual transmission partners (18)(19)(20). In contrast, a more significant VL correlation was shown for a transmission pair cohort of men who have sex with men (MSM) in San Francisco (21), and a phylogenetic analysis of MSM in the Swiss HIV Cohort Study concluded that up to half of the variance in set-point VL can be heritable (22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Host factors ranged from coreceptor gene (e.g., CCR5) polymorphisms to HLA variants (24,50,83,84). The importance of viral characteristics is reflected by a correlation between donor and recipient VL after controlling for the effects of age and gender, as well as HLA (85). Supporting evidence from several recent studies suggests that the magnitude of the influence of the transmitted virus on the recipient's VL can be highly variable (26,27).…”
mentioning
confidence: 99%
“…We and others have reported previously that both host and viral factors can independently impact HIV-1 VL during the early and chronic phases of infection (54,81,84,85). Host factors ranged from coreceptor gene (e.g., CCR5) polymorphisms to HLA variants (24,50,83,84).…”
mentioning
confidence: 99%